The Volume-Regulated Anion Channel LRRC8 is Involved in the Initiation of Epidermal Differentiation and is Deregulated in Psoriasis - Magdalena Jahn; Victoria Lang; Oliver Rauh; Torsten Fauth; Claudia Buerger (JID Innovations)
Recent studies have shown that LRRC8A, the essential subunit of the volume-regulated anion channel LRRC8, which is responsible for mediating cell volume regulation during hypotonic stress, is predominantly localized in the basal layer of the epidermis. This prompted us to investigate whether LRRC8A plays a role in maintaining epidermal homeostasis by regulating key processes initiated in this layer, such as cell proliferation and/or differentiation.LRRC8A was found to be strongly upregulated in transiently amplifying cells at the onset of differentiation. While LRRC8A mRNA remains high when keratinocytes mature further, the LRRC8A protein is drastically downregulated. Interference with LRRC8A expression at this step inhibits the transition of keratinocyte stem cells into transiently amplifying cells and impairs terminal differentiation. As psoriasis is a common chronic inflammatory skin disease characterized by disturbed epidermal differentiation and aberrant function of transiently amplifying cells, we investigated the involvement of LRRC8A in this disease. Indeed, LRRC8A was strongly decreased in lesional psoriatic skin, which could also be mimicked in vitro using Th1/Th17 cytokine mixes. Thus, our data suggest that LRRC8 could serve as a therapeutic target for the topical treatment strategies of psoriatic lesions by restoring the capacity of keratinocytes to initiate differentiation.